Correlation of serum creatine phosphokinase and serum cholinesterase in organophosphate poisoning in children - K., Dhanalakshmi; K., Febina; Sabapathy, Sarala; R., Chaithra; N., Thileepan (International Journal of Contemporary Pediatrics, 2019)
Background: Organophosphate (OP) poisoning is one of the most common pesticide poisoning in India in adolescents because of its easy availability. Serum pseudocholinesterase levels are commonly used to assess the severity and to know the prognosis in OP compound poisoning. Serum creatine phosphokinase (CPK) levels is another lab parameter which gets deranged in OP poisoning and has been tried in adults to assess the severity and to know the prognosis. Authors objective was to study the correlation of serum pseudocholinesterase and serum CPK in organophosphate poisoning at admission and to compare outcome with serum CPK levels. Methods: All the children in the age group of 1 month to 18 yrs, who were admitted with the history of suspected OP compound poisoning were enrolled for the study. Estimation of cholinesterase and CPK levels were done at admission and after 1 week. Patients were categorised in to latent, mild, moderate and severe cases based on the S. Cholinesterase levels. These values were analysed to see the correlation. Results: Among 34 OP poisoning cases,13(38%) were males and 21(62%) were females. Mean age of study population was12.6+4.25 yrs. The median CPK values in latent, mild, moderate and severe cases were 121.5 IU/L,276.5 IU/L, 308IU/L and 467IU/L respectively (p=0.015). Spearman’s rho Correlation coefficient was -0.522 between S. Cholinesterase and S CPK at admission which was significant. The median serum CPK level after 1week in non survivors was 2498.0IU/L and in survivors was 201.0IU/L (p0.014). Conclusions: There was a strong negative relationship between serum cholinesterase and serum CPK at admission in OP poisoning. Follow up values at 1 week showed that significantly high serum CPK and low cholinesterase, which was also significant and was associated with mortality.